ANALISIS INDEKS KEPUASAN MASYARAKAT (IKM) TERHADAP PELAYANAN PUBLIK DI PUSKESMAS XXX - Zulfida Hariany; a. Rahim Matondang (Departemen Teknik Industri Universitas Sumatera Utara, 2014)
The satisfaction of the community is a very important factor and determines the success of a business entity because the public are consumers of the products or services it generates. Problems found in the study are the complaints about the lack of visitors going to the Ministry as well as the facilities and infrastructure that are going on in Clinics XXX, so the impact on the number of visitors Clinics XXX. This study aims to analyze the quality of service provided to the public health center or community XXX and to determine the level of conformity between the performance of the Ministry of public health with the hope of Community importance or use of the service. Analysis tools are used is to use the community's Satisfaction Index (IKM). Community satisfaction (IKM) is calculated using the weighted average value of each item of service in accordance with the decision of the Minister for Administrative Reform No. 25 of 2004. The methods used to determine the level of conformity is a method of Importance Performance Analysis (IPA). The Research Community Satisfaction Index measurement (IKM) indicates the quality of the given services Clinics XXX still less well, based on the average value of the elements of each service unit at the clinic. Form comparisons between expectations and performance service levels, there are some elements that should be prioritized as elements of service, speed and discipline because in fact the community still feel lack of discipline employees of clinics in serving the community.